Integrasi Kultural dan Teknologi dalam Membangun Partisipasi Stakeholder dalam Penggalangan Dana untuk Sekolah Negeri - Nurul Ratna Sari; Megan Lee (JAST : Jurnal Aplikasi Sains dan Teknologi, 2026)
In Australia, a four-season country, air-conditioning is a vital learning facility to cooling the class in summer and warming it in autumn, winter, and spring. A public primary school in WA is not included in the current prioritisation but needs to replace 12 poorly functioning air-conditioning units in its classrooms. However, the school’s budget cannot cover the air-conditioning replacement cost and the school is unable to conduct their own fundraising. Thus, the community service of Parents and Citizens Association of the school conducted fundraising. The event integrates communication technology and sausage sizzle fundraising at a major chain Australian hardware store, Bunnings. Sausage sizzle is an Australian cultural icon, which represent community spirit. To reach stakeholders, the event uses a website for donation, QR code, online flier, and the school and parents’ communication portal. The participating stakeholders were four stakeholders from industry (three local supermarkets and a sausage producer), 15 volunteers from parents and the local community. The online and offline fundraising resulted total AUD $5678. The school’s Parents and Citizens Association managed communication with three government representatives that accelerate the approval of government budget for air-conditioning replacement at the school. The fundraising demonstrates best practice in community service by integrating local community customs and communication technology in involving stakeholders. ABSTRAKDi Australia, negara dengan empat musim, Air Conditioner (AC) merupakan fasilitas pembelajaran yang vital untuk menyejukkan ruang kelas ketika musim panas yang ekstrim dan menghangatkan ketika musim gugur, dingin, dan semi. Sebuah sekolah negeri di Australia Barat tidak berada dalam prioritas pendanaan Pemerintah, tetapi membutuhkan penggantian 12 AC yang usang dan temperaturnya tidak optimal. Anggaran sekolah tidak mencukupi penggantian AC dan sekolah negeri tidak dapat melakukan penggalangan dana. Maka, Asosiasi orang tua dan warga negara untuk sekolah tersebut melakukan penggalangan dana. Kegiatan ini mengintegrasikan penggunaan teknologi komunikasi dan penjualan makanan lokal Australia yaitu roti sosis bakar (sausage sizzle), di sebuah toko perkakas utama di Australia, Bunnings. Sausage sizzle merupakan suatu ikon budaya Australia, yang menyimbolkan semangat komunitas. Untuk menjangkau partisipasi stakeholder, kegiatan dilakukan melalui media online berupa website donasi, QR Code, flier online, dan penggunaan aplikasi komunikasi. Penggalangan dana berhasil melibatkan empat stakeholder industri, 15 sukarelawan dari orang tua murid, dan masyarakat di sekitar lokasi kegiatan. Penggalangan dana online dan offline mengumpulkan dana total AUD $5678. Asosiasi orang tua dan warga negara juga menjalin komunikasi dengan tiga perwakilan pemerintah lokal yang berdampak pada percepatan persetujuan alokasi anggaran pemerintah untuk penggantian AC. Kegiatan ini menunjukkan praktek baik pengabdian masyarakat yang mengintegrasikan budaya lokal dan teknologi komunikasi dalam pelibatan stakeholder.